Interleukin 4 inducible 1 gene (IL4I1) is induced in chicken phagocytes by Salmonella Enteritidis infection - Elsheimer-Matulova, Marta; Polansky, Ondrej; Seidlerova, Zuzana; Varmuzova, Karolina; Stepanova, Hana; Fedr, Radek; Rychlik, Ivan (Veterinary research, 2020)
In attempt to identify genes that are induced in chickens by Salmonella Enteritidis we identified a new highly inducible gene, interleukin 4 induced 1 gene (IL4I1). IL4I1 reached its peak expression (458× induction) in the cecum of newly hatched chickens 4 days post-infection and remained upregulated for an additional 10 days. IL4I1 was expressed and induced in macrophages and granulocytes, both at the mRNA and protein level. IL4I1 was expressed and induced also in CD4 and γδ T-lymphocytes though at a 50-fold lower level than in phagocytes. Expression of IL4I1 was not detected in CD8 T lymphocytes or B lymphocytes. Mutation of IL4I1 in chicken HD11 macrophages did not affect their bactericidal capacity against S. Enteritidis but negatively affected their oxidative burst after PMA stimulation. We therefore propose that IL4I1 is not directly involved in bactericidal activity of phagocytes and, instead, it is likely involved in the control of inflammatory response and signaling to T and B lymphocytes.
Keywords: Leukocytes; cékum; Salmonella enteritidis; nemoci drůbeže; mužské pohlaví; Avian Proteins; oxidasa L-aminokyselin; kur domácí; slezina; Chickens; zvířata; Poultry Diseases; ptačí proteiny; L-Amino Acid Oxidase; Phagocytes; Cecum; leukocyty; fagocyty; salmonelová infekce u zvířat; Spleen; Salmonella Infections, Animal; Male; Animals